Análisis de facies de la Capa de Oolitos ferruginosos de Arroyofrío en la Sierra de Arcos (Jurásico, Cordillera Ibérica septentrional) - Ramajo, J.; Aurell, M.; Cepría, J. (Journal of Iberian Geology, 2002)
In this work we have studied the Arroyofrio Bed. This is a classic and largely studied ironstone unit in the Iberian Range. The age of this bed ranges from the Lower Callovian to Middle Oxfordian. This is a complex lithologic unit formed by irregular sedimentary events and several discontinuities associated with stratigraphic gaps of variable extent. In this work five facies containing ferruginous ooids are described and a preliminary study of the carbonate cements and Fe oolite facies is presented. This ironstone bed was formed near to an emergent high (Ejulve high). The oolites formed in a shallow marine subtidal environment. The facies and cement analysis shows that there were no long episodes of subaereal exposure at the Callovian-Oxfordian boundary. These data also demonstrate that these sediments were not deposited in deep marine conditions. The most probable hypothesis is that Fe ooids were formed in shallow subtidal and perhaps intertidal conditions and that they were eventually transported into more distal and relatively deep basinal areas.